Pengaruh Model Pembelajaran Kooperatif Tipe Jigsaw Terhadap Hasil Belajar Ilmu Pengetahuan Sosial Pada Siswa Sekolah Dasar - Hakiki, Nurul; Kaharuddin, Kaharuddin; Rahmat, Yusran (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
The primary aim of this study was to examine the impact of the Jigsaw cooperative learning model on the learning outcomes of Social Studies (IPS) among fifth-grade students at SDN 148 Bonto Bulaeng, Kabupaten Bulukumba. This research adopted a pre-experimental design, specifically a quasi-experimental design, and utilized a quantitative approach. A sample of 12 students was selected for the study. Data collection was conducted through learning outcome tests and observation sheets, while data analysis employed descriptive analysis and T-Test statistical methods. The findings revealed a significant improvement in the students' Social Studies learning outcomes post-implementation of the Jigsaw cooperative learning model. Initially, the average pretest score was 59, which increased to an average posttest score of 83. The T-Test analysis further confirmed the positive effect of the Jigsaw model on learning outcomes, with a significance value of 0.010, which is below the alpha value of 0.05 (0.010 < 0.05). Thus, the study concluded that the Jigsaw cooperative learning model significantly enhances learning outcomes in Social Studies for fifth-grade students, leading to the rejection of the null hypothesis (H0) and acceptance of the alternative hypothesis (H1).